Screening and construction of nanobodies against human CD93 using phage libraries and study of their antiangiogenic effects - Miao, Hui; Wu, Yiling; Ouyang, Hao; Zhang, Peiwen; Zheng, Wenyun; Ma, Xingyuan (Frontiers in Bioengineering and Biotechnology, 2024)
Background Cluster of Differentiation 93 (CD93) plays an important role in angiogenesis and is considered an important target for inhibiting tumor angiogenesis, but there are currently no therapeutic antibodies against CD93 in the clinic. Thus, we describe the screening of novel nanobodies (Nbs) targeting human CD93 from a phage library of shark -derived Nbs. Methods Screening and enrichment of phage libraries by enzyme-linked immunosorbent assay (ELISA). Anti-CD93 Nbs were purified by expression in E. coli. The binding affinity of anti-CD93 Nbs NC81/NC89 for CD93 was examined by flow cytometry (FC) and ELISA. The thermal stability of NC81/NC89 was examined by ELISA and CD spectroscopy. Afterward, the anti-angiogenic ability of NC81/NC89 was examined by MTT, wound healing assay, and tube formation assay. The expression level of VEcadherin (VE-Ca) and CD93 was detected by Western Blot (WB). The binding sites and binding forms of NC81/NC89 to CD93 were analyzed by molecular docking.The anti-CD93 Nbs were screened in a phage library, expressed in E. coli, and purified to >95% purity. The results of FC and ELISA showed that NC81/NC89 have binding ability to human umbilical vein endothelial cells (HUVECs). The results of ELISA and CD spectroscopy showed that NC81/NC89 retained the ability to bind CD93 at 80°C and that the secondary structure remained stable. In vitro, the results showed that NC81 and NC89 significantly inhibited the proliferation and migration of human umbilical vein endothelial cells (HUVECs) as well as tube formation on Matrigel. Western Blot showed that NC81 and NC89 also inhibited the expression of VE-Ca thereby increasing vascular permeability. It was found during molecular docking that the CDR regions of NC81 and NC89 could be attached to CD93 by strong hydrogen bonds and salt bridges, and the binding sites were different.We have successfully isolated NC81 and NC89, which bind CD93, and both Nbs significantly inhibit angiogenesis and increase vascular permeability. These results suggest that NC81 and NC89 have potential clinical applications in angiogenesis-related therapies.